2018
DOI: 10.1039/c7nj03026f
|View full text |Cite
|
Sign up to set email alerts
|

A rationally designed perfluorinated host for the extraction of PFOA from water utilising non-covalent interactions

Abstract: Three hosts for the encapsulation of perfluorooctanoic acid have been synthesized. The host:guest complexes have been characterized by multinuclear NMR spectroscopy in solution and the solid state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 167 publications
0
14
0
Order By: Relevance
“…Supramolecular chemistry represents an elegant approach to construct multifunctional materials for challenging applications 33,34 , with the virtues of molecular recognition and self-assembly. Macrocyclic hosts, such as crown ether 35 , cyclodextrin 36 , calixarene 3740 , pillararene 41,42 , cucurbituril 43,44 , and others 45,46 , are families of well-studied artificial receptors with a cavity that can be selective for the recognition of particular guests. Efficient molecular recognition by macrocycles in aqueous media has been demonstrated for various applications, including the detection 44,47 and absorption 48,49 of pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular chemistry represents an elegant approach to construct multifunctional materials for challenging applications 33,34 , with the virtues of molecular recognition and self-assembly. Macrocyclic hosts, such as crown ether 35 , cyclodextrin 36 , calixarene 3740 , pillararene 41,42 , cucurbituril 43,44 , and others 45,46 , are families of well-studied artificial receptors with a cavity that can be selective for the recognition of particular guests. Efficient molecular recognition by macrocycles in aqueous media has been demonstrated for various applications, including the detection 44,47 and absorption 48,49 of pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…The C=O (carbonyl) bond length is 1.23 and C-O (hydroxyl) 1.289 Å, which is well comparable to anhydrous PDFO, [49] with 4 molecules in the asymmetric unit, where the corresponding bond lengths range from 1.228 to 1.241 and from 1.288 to 1.331, respectively. The C-C distances in the PDFO chain are all very close to 1.56 Å (from 1.557 to 1.565 Å), which is in average a little longer than the average in the anhydrous PDFO (1.54 Å), but well within the range found therein (1.510 to 1.576 Å).…”
Section: Resultsmentioning
confidence: 55%
“…The fit improved considerably (Rwp dropped from 12.7 to 8.5 %), but subsequent crystallochemical analysis of the refined structure and calculation of its energy revealed that the structure was in fact "spoiled" by the described refinement procedure. Although the molecules were moved only slightly, the H-bonds pattern was destroyed (disregarding the positions of hydrogen atoms) and also the intermolecular F-F contacts in the hydrophobic part of the structure were less similar to those in the related structures (for example anhydrous PDFO [49] ). This was more or less expected due to the limited quality of the powder pattern, as described above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the findings of Omorodion et al, who studied the nature of non-covalent interactions in calixarene-PFOA hostguest complexes, 29 we speculated that the primary interaction responsible for the successful adsorption of PFOA by the polymers is the hydrogen bond between the carboxylic group of PFOA and a hydroxyl oxygen of the calixarene. We also surmise that additional stabilization may be achieved by C-F••••F-C interactions 39 between PFOA and the fluorinated linkers in FCX4-P and FCX4-BP.…”
Section: Resultsmentioning
confidence: 81%